Thermal Properties and Crystallinity of Thermotropic Liquid Crystalline Copolyesters Prepared from Poly(ethylene terephtalate) (PET) and Rigid Aromatic Units - Tan, Abdullah; Altinok, Eaydar; Yerlikaya, Zekeriya; Aksoy, Serpil (Informa UK Limited, 2007)
A series of copolyesters were synthesized by melt‐polycondensation reaction of poly(ethylene terephtalate) (PET) with various proportions of equimolar compositions of p‐acetoxybenzoic acid (p‐ABA), hydroquinone diacetate (HQDA) and terephtalic acid (TPA). Viscosity, liquid crystallinity, thermal properties, degree of crystallinity and thermal stabilitiy of these copolyesters were investigated by Ubbelohde viscometer, hot‐stage polarized light microscopy (PLM), differential scanning calorimetry (DSC), wide‐angle X‐ray diffraction (WAXD) and thermogravimetric analysis (TGA), respectively. On the basis of viscosity measurement, it was observed that intrinsic viscosity values of the copolyesters are increased regularly with increasing amounts of aromatic units (p‐ABA, HQDA and TPA) in the polymer chain. Thermotropic liquid crystalline behavior was observed in the copolyesters containing over 50 mol% of rigid p‐ABA/HQDA/TPA aromatic units. DSC analysis of the anisotropic copolyesters revealed broad and weak en...
Keywords: copolymerization; liquid-crystalline copolyester; thermal properties; poly(ethylene terephthalate); crystallinity